Bowel and bladder function after resection of deeply infiltrating endometriosis. (21st May 2014) - Li, Ying Hong; De Vries, Bradley; Cooper, Michael; Krishnan, Surya
<x xml:space="preserve">Abstract</x> Aims To compare bowel and bladder function following uterosacral or rectovaginal excision of endometriosis with excision of endometriosis from other sites of the pelvis. Methods A retrospective cohort study was performed via a questionnaire derived from validated questionnaires in the literature. This was applied to the two groups of women who have had endometriosis resected in the last 15 years – those with deeply infiltrating endometriosis (DIE) and those with endometriosis from other sites. In the questionnaire, voiding dysfunction, urinary stress incontinence, urinary urge incontinence, stool evacuation and overall symptoms post‐surgery were investigated. The higher the score, the higher the level of dysfunction. Results Women with DIE had higher levels of urinary stress dysfunction than the control group (mean 1 vs 0, IQR 3 vs 2, P = 0.047). Women with DIE also expressed a higher level of bowel dysfunction (mean 2 vs 2, IQR 1 vs 0, P = 0.002). However, women with DIE also reported significant improvement in urinary and bowel dysfunction postoperatively. There were no significant differences between the other variables. Conclusion The study demonstrated no clear association between the depth of excision of endometriosis with urinary and bowel dysfunction. The differences in urinary stress incontinence and bowel dysfunction may be explained by DIE itself causing damage to the hypogastric plexus.